Coupling bio-logging with nutritional geometry to reveal novel insights into the foraging behaviour of a plunge-diving marine predator. Issue 3 (2nd July 2016) - Machovsky-Capuska, Gabriel E; Priddel, David; Leong, Philip HW; Jones, Peter; Carlile, Nicholas; Shannon, Lesley; Portelli, Dean; McEwan, Alistair; Chaves, Alexandre V; Raubenheimer, David
ABSTRACT: It is widely believed that predators maximise their energy intake while foraging and consume prey that are nutritionally similar. We combined GPS data loggers, miniaturised cameras, dietary sampling and nutritional geometry to examine the nutritional variability in the prey and selected diet, and foraging performance, of the masked booby ( Sula dactylatra tasmani ), a wild carnivore and marine top predator. Data loggers also revealed no significant differences between sexes in the foraging performance of chick-rearing adults. Females provided more food to their chicks than the males and, regardless of the nutritional variability of prey consumed, both sexes showed similar amounts of protein and lipid in their diets. Miniaturised cameras combined with nutritional analysis of prey provided, for the first time, fine-scale detail of the amounts of macronutrients consumed in each plunge dive and the overall foraging trip. Our methodology could be considered for future studies that aim to contribute to the general understanding of the behavioural and physiological mechanisms and ecological and evolutionary significance of animal foraging (e.g. energy expenditure budgets and prey selection for self- and offspring-feeding that could lead to sex-specific foraging strategies).